2009
DOI: 10.1111/j.1526-4637.2009.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Catastrophizing in the Prediction of Postoperative Pain

Abstract: The present study findings suggest that it is possible to preoperatively identify patients at risk for experiencing more severe pain in the postoperative recovery period. In such cases, consideration might be given to utilizing a variety of resources to ameliorate or prevent pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
99
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(121 citation statements)
references
References 37 publications
15
99
3
4
Order By: Relevance
“…Papaioannou et al evaluated PCS scores in patients who underwent lumbar disc fusion within 3 age groups: 20-40, 40-60, and >60 years old. They did not find any correlation between age and PCS scores (14). The same results, in which there was no correlation between age and PCS or PCS subscale scores, were obtained in the present study, as well.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Papaioannou et al evaluated PCS scores in patients who underwent lumbar disc fusion within 3 age groups: 20-40, 40-60, and >60 years old. They did not find any correlation between age and PCS scores (14). The same results, in which there was no correlation between age and PCS or PCS subscale scores, were obtained in the present study, as well.…”
Section: Discussionsupporting
confidence: 77%
“…Postoperative pain is a troublesome condition for patients, their relatives, doctors, health institutions, and governments. The levels of PCS scores were found to positively correlate with the severity of postoperative pain (1,14). It has been suggested that patients with higher PCS scores were also those who consumed higher amounts of analgesics and whose pain was most likely to become chronic and severe (1,3,29).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…2,3 For that reason, we listed cyclosporine as third-line therapy for patients with concurrent hepatitis C and psoriasis. 4 We noted that there have been several case reports of successful treatment of psoriasis in patients with hepatitis C treated with cyclosporine without significant clinical adverse events. We also cited two studies in which liver biopsy findings after cyclosporine therapy did not worsen in psoriasis patients with concomitant hepatitis C infection.…”
mentioning
confidence: 97%
“…High scores have been shown to be associated with more intense pain, depression, anxiety, pain behavior, disability, more analgesic consumption, and more prolonged hospital stays. Groups studied include breast surgery, 3 orthopaedic, 4 and general surgical 5 patients. I have found use of the PCS helpful in clinical practice.…”
mentioning
confidence: 99%